Simulation of the hydrodynamic conditions of the eye to better reproduce the drug release from hydrogel contact lenses: experiments and modeling - Pimenta, A. F. R. (2018)
The final publication is available at Springer via http://dx.doi.org/10.1007/s13346-016-0303-1